2010
DOI: 10.1007/s10802-009-9381-6
|View full text |Cite
|
Sign up to set email alerts
|

Emotional/Behavioral Problems and Functional Impairment in Clinic- and Community-Based Children with Attention-Deficit/Hyperactivity Disorder in Taiwan

Abstract: Using a sample of 268 patients and 137 community-based children with DSM-IV ADHD, and 268 school controls, aged 6-15, this study aimed to compare the emotional/behavioral problems and functional impairment between clinic- and community-based children with ADHD. Children's ADHD-related symptoms, a wide range of emotional/behavioral problems, and functional impairments were assessed by the psychiatric interviews and self-, parent- and teacher-reported questionnaires. Both ADHD groups scored higher in parent- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
2
16
1
Order By: Relevance
“…In this context, it has been claimed that, due to its strong genetic component, parents of affected children may be more likely to have had ADHD themselves and, as a consequence, to have not been able to achieve higher education levels [41]. In contrast, the observation that a higher level of maternal education was associated with a greater prevalence of ADHD in offspring has not been reported before; but it is consistent with what Gau et al [42] have found: a positive association between the number of psychiatric referrals and higher maternal education levels in children with ADHD. This, in turn, suggests that mothers of higher education may be more likely to be aware of their children’s problematic behaviours and have more knowledge about ADHD.…”
Section: Discussionsupporting
confidence: 85%
“…In this context, it has been claimed that, due to its strong genetic component, parents of affected children may be more likely to have had ADHD themselves and, as a consequence, to have not been able to achieve higher education levels [41]. In contrast, the observation that a higher level of maternal education was associated with a greater prevalence of ADHD in offspring has not been reported before; but it is consistent with what Gau et al [42] have found: a positive association between the number of psychiatric referrals and higher maternal education levels in children with ADHD. This, in turn, suggests that mothers of higher education may be more likely to be aware of their children’s problematic behaviours and have more knowledge about ADHD.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it is not possible to determine whether this sample also represents other children that were not recruited and whether cooperation is confounded with ADHD variables. This limitation is typical to most clinic-based ADHD studies around the world (Lee and Ousley, 2006; Gau et al, 2010). Another limitation of the study is the exclusion of ADHD children with severe comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies, however, reported rates or levels of functional impairment. Researchers have assessed functional impairment in relation to specific disorders in other Asian countries (e.g., ADHD in Taiwan [19]; war-related PTSD in Sri Lanka [20], but not global functional impairment.…”
Section: Introductionmentioning
confidence: 99%